Pottery from the University of California, Berkeley Excavations in the Area of the Maški Gate (MG22), Nineveh, 1989-1990 - Barbanes Wilkinson, Eleanor; Lumsden, Stephen (Archaeopress Publishing Ltd, 2022)
Nineveh, Iraq, is one of the longest occupied cities in the world, dating at least back to the mid-7th millennium BC. UC Berkeley excavations uncovered a district of large dwellings and wide streets near the Maski Gate (MG22), providing a stratigraphic history of Late Assyrian ceramics at the centre of the empire through to the 7th century BC.